A systematic review of instruments aimed at evaluating metered-dose inhaler administration technique in children (2021)
The objective of the present study was to perform a systematic review of instruments aimed at evaluating pressurized metered-dose inhaler (pMDI) administration technique in children and evaluating the measurement properties of these instruments. A systematic search of the literature was performed in order to identify studies in which an instrument (scale, checklist, or questionnaire) for evaluating pMDI administration technique in children was described. Instruments were evaluated based on their reliability, validity, utility, endorsement frequency, restrictions in range, comprehension, lack of ambiguity, and lack of value-laden or offensive content. A total of 24 instruments were identified. The age of the children ranged from 1 month to 18 years, the number of steps or items included in the instruments ranged from 3 to 21, and nearly half of the instruments distinguished between essential and non-essential steps or items. In only 7 of the 24 instruments was there a report of their measurement properties, mainly reliability and utility. Taking into consideration the information contained in the instruments, as well as their measurement properties, we determined four instruments to be the best of the available ones. Among the 24 instruments for the assessment of pMDI administration technique in children that were identified and systematically examined, four were considered to be the best ones available. However, additional evaluation of their measurement properties should be done before using them in clinical practice and for research purposes.